2021
DOI: 10.1111/iji.12535
|View full text |Cite
|
Sign up to set email alerts
|

Association of single‐nucleotide polymorphisms in tumour necrosis factor and human leukocyte antigens genes with type 1 diabetes

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by progressive destruction of insulin‐producing pancreatic beta cells. This multifactorial disease has a strong genetic component associated with the human leukocyte antigens (HLA) and non‐HLA regions. In this study, we compared frequencies of HLA‐DRB1 alleles and single‐nucleotide polymorphisms (SNPs) associated the genes coding for: toll‐like receptors (TLRs), tumour necrosis factor (TNF), interleukin‐1 (IL‐1), interleukin‐1 receptor type 1 (IL‐1R1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Within the context of the simplistic paradigm whereby autoimmune diseases are facilitated by an imbalance between anti-inflammatory (IL-4, IL-10, IL-13) and proinflammatory cytokines (TNF-α, IFN-γ) low levels of the former and high levels of the latter facilitate T1DM onset (Moudgil and Chouby 2011) 39 . Both our former finding (Osman et al 2021), 37 that T1DM was associated with high TNF producer genes (rs361525), and current findings of low IL-4 producer genes are consistent with this model.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Within the context of the simplistic paradigm whereby autoimmune diseases are facilitated by an imbalance between anti-inflammatory (IL-4, IL-10, IL-13) and proinflammatory cytokines (TNF-α, IFN-γ) low levels of the former and high levels of the latter facilitate T1DM onset (Moudgil and Chouby 2011) 39 . Both our former finding (Osman et al 2021), 37 that T1DM was associated with high TNF producer genes (rs361525), and current findings of low IL-4 producer genes are consistent with this model.…”
Section: Discussionsupporting
confidence: 89%
“…Of 180 patients with T1DM, 90 (50%) were females (aged 3-28) and 90 (50%) were males (aged [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The age of onset of T1DM was below 13 years in 142 (78.9%) and above 13 in 34 (18.1%) patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprising of six exons and five introns, the IL-18 gene is located on chromosome 11q22.2-q22.3 ( 152 ). Several IL-18 polymorphisms have been identified, however the genetic relationship between single nucleotide polymorphisms (SNPs) at positions-137, -607 in IL-18 gene promoter and T1D have been of interest and is widely reported in previous studies ( 153 ). Conversely, other studies failed to show any association between T1D and these SNPs.…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…More research is needed to understand the role of IL2RA gene variants in the development of vascular complications in people with T1DM; however, recent findings suggest that IL2RA gene variants may be a target for the development of new treatments for these complications, and could confer risk alleles for T1DM among the Emirati population [27]. In a study published in 2021, Osman A. E. and colleagues [23] investigated the levels of ILs in patients with T1DM and healthy controls. They found that the levels of IL-1A/B, IL-2, and IL-12 were significantly higher in patients with T1DM in contrast to healthy controls.…”
Section: Discussionmentioning
confidence: 99%